Rapid response of hyperkeratotic erythema multiforme to oclacitinib in two dogs. Issue 4 (19th April 2020) - High, Endya J.; Linder, Keith E.; Mamo, Lisa B.; Levy, Britt J.; Herrmann, Ina; Bizikova, Petra
Abstract : Background: Hyperkeratotic erythema multiforme (HKEM) is a clinically distinct dermatosis and poorly characterized syndrome, comprised of hyperkeratotic plaques with variable symmetry and apoptosis similar to "classic" erosive canine EM. Hyperkeratotic EM has a protracted clinical course and, although treatments with glucocorticoids, azathioprine and/or ciclosporin have been tried, rates of remission are low. Objectives: To describe successful treatment of HKEM in two dogs using oclacitinib. Animals: A 7‐year‐old, spayed Havanese dog (Case 1) and a 1‐year‐old, intact cryptorchid Dachshund dog (Case 2). Methods: Case characterization and clinical diagnoses were based on lesion character, surgical biopsy, cytological evaluation, culture, direct immunofluorescence (DIF) and expected responses to treatments. Results: Both cases exhibited multifocal, often symmetrical hyperkeratotic plaques with adherent scale. Histological findings revealed prominent epidermal hyperplasia, parakeratotic hyperkeratosis, lymphocytic dermatitis and transepidermal apoptosis with lymphocytic satellitosis. DIF revealed fine, patchy IgG, IgM and IgA basement membrane deposits (Case 2). Both dogs exhibited rapid improvement with oral oclacitinib (0.6–0.9 mg/kg twice daily) with a complete remission of clinical signs observed in 12 and seven weeks in cases 1 and 2, respectively. Conclusion and Clinical Importance: Oclacitinib could be considered as a fast‐acting and effective treatment option for HKEM in dogs. Abstract : Background – Hyperkeratotic erythema multiforme (HKEM) is a clinically distinct dermatosis and poorly characterized syndrome, comprised of hyperkeratotic plaques with variable symmetry and apoptosis similar to "classic" erosive canine EM. Hyperkeratotic EM has a protracted clinical course and, although treatments with glucocorticoids, azathioprine and/or ciclosporin have been tried, rates of remission are low. Objectives – To describe successful treatment of HKEM in two dogs using oclacitinib. Conclusion and Clinical Importance – Oclacitinib could be considered as a fast‐acting and effective treatment option for HKEM in dogs. Résumé: Contexte: L'érythème polymorphe hyperkératosique (HKEM) est une dermatose cliniquement distincte et un syndrome peu caractérisé, comprenant des plaques hyperkératosiques de symétrie variable et de l'apoptose semblable à l'EM canine érosive « classique ». L'EM hyperkératosique a une évolution clinique au long cours et bien que des traitements avec corticoïdes, azathioprine et/ou ciclosporine aient été essayés, les taux de rémission sont faibles. Objectifs: Décrire un traitement efficace de l'HKEM chez deux chiens à l'aide d'oclacitinib. Sujets: Un chien bichon havanais de 7 ans (Cas 1) et un teckel cryptorchide entier de 1 an (Cas 2). Méthodes: La caractérisation du cas et le diagnostic clinique ont été basés sur les lésions, les biopsies, la cytologie, la culture, l'immunofluorescence directe (DIF) et les réponses attendues aux traitements. Résultats: Les deux cas ont montré des plaques hyperkératosiques, souvent symétriques, multifocales avec squames adhérentes. Les données histologiques ont montré une hyperplasie épidermique proéminente, de l'hyperkératose parakératosique, une dermatite lymphocytaire et de l'apoptose transépidermique avec satellitose lymphocytaire. Le DIF a révélé des dépôts en patch d'IgG, IgM et IgA sur la membrane basale (Cas 2). Les deux chiens ont montré une amélioration rapide avec de l'oclacitinib oral (0.6–0.9 mg/kg deux fois par jour) avec rémission complète des signes cliniques observés en 12 et sept semaines respectivement dans les cas 1 et 2. Conclusion et importance clinique: L'oclacitinib pourrait être considéré comme une option thérapeutique rapide et efficace pour l'HKEM chez le chien. Resumen: Introducción: el eritema multiforme hiperqueratótico (HKEM) es una dermatosis clínicamente distinta y un síndrome mal caracterizado, compuesto por placas hiperqueratóticas con simetría variable y apoptosis similar a la EM canina erosiva "clásica". La EM hiperqueratótica tiene un curso clínico prolongado y, aunque se han intentado tratamientos con glucocorticoides, azatioprina y/o ciclosporina, las tasas de remisión son bajas. Objetivos: describir el tratamiento exitoso de HKEM en dos perros tratados con oclacitinib. Animales: un perro Havanés esterilizado de 7 años de edad (caso 1) y un perro Dachshund criptórquido intacto de 1 año de edad (caso 2). Métodos: la caracterización de casos y los diagnósticos clínicos se basaron en el carácter de la lesión, la biopsia quirúrgica, la evaluación citológica, el cultivo, la inmunofluorescencia directa (DIF) y las respuestas esperadas a los tratamientos. Resultados: ambos casos exhibieron placas hiperqueratóticas multifocales, a menudo simétricas, con escamas adherentes. Los hallazgos histológicos revelaron hiperplasia epidérmica prominente, hiperqueratosis paraqueratótica, dermatitis linfocítica y apoptosis transepidérmica con satelitósis linfocítica. DIF reveló depósitos de membrana basal IgG, IgM e IgA finas y discontinuas (Caso 2). Ambos perros mostraron una mejoría rápida con oclacitinib oral (0, 6‐0, 9 mg/kg dos veces al día) con una remisión completa de los signos clínicos observados en 12 y siete semanas en los casos 1 y 2, respectivamente. Conclusión e importancia clínica: Oclacitinib podría considerarse como una opción de tratamiento de acción rápida y eficaz para HKEM en perros. Zusammenfassung: Hintergrund: Das hyperkeratotische Erythema multiforme (HKEM) ist eine klinisch deutlich abgegrenzte Dermatose, aber ein schlecht beschriebenes Syndrom, welches aus hyperkeratotischen Plaques mit unterschiedlicher Symmetrie und Apoptose, ähnlich dem „klassischen" erosiven EM des Hundes, besteht. Das hyperkeratotische EM zeigt einen langwierigen klinischen Verlauf und, obwohl Behandlungen mit Glukokortikoiden, Azathioprin und/oder Ciclosporin versucht worden sind, sind die Remissionsraten niedrig. Ziele: Die Beschreibung einer erfolgreichen Behandlung von HKEM bei zwei Hunden mittels Oclacitinib. Tiere: Eine 7 Jahre alte kastrierte Havaneserhündin (Fall 1) und ein 1 Jahre alter intakter kryptorchider Dackelrüde (Fall 2). Methoden: Die Fallbeschreibung sowie die Beschreibung der klinischen Diagnosen basierte auf dem Aussehen der Läsionen, der chirurgischen Biopsie, der zytologischen Evaluierung, der Kultur, der direkten Immunfluoreszenz (DIF) und der erwarteten Behandlungserfolge. Ergebnisse: Beide Fälle zeigten multifokale, oft symmetrische hyperkeratotische Plaques mit anhaftenden Schuppen. Die histologischen Befunde zeigten eine prominente epidermale Hyperplasie, eine parakeratotische Hyperkeratose, eine lymphozytäre Dermatitis und eine transepidermale Apoptose mit lymphozytärer Satellitenbildung. Die DIF zeigte feine, fleckige Ablagerungen von IgG, IgM und IgA in der Basalmembran (Fall 2). Beide Hunde zeigten eine schnelle Verbesserung mit Oclacitinib per os (0, 6‐0, 9 mg/kg zweimal täglich), wobei eine völlige Remission der klinischen Zeichen innerhalb von 12 bzw sieben Wochen in den Fällen 1 bzw 2 gesehen wurden. Schlussfolgerung und klinische Bedeutung: Oclacitinib könnte als schnell‐wirkende und wirksame Behandlungsoption für HKEM bei Hunden in Frage kommen. 要約: 背景: 過角化性多形紅斑(HKEM)は、臨床的に異なる皮膚疾患であり、対称性で可変的な過角化性性局面および「古典的な」犬のびらん性EMに類似したアポトーシスで構成される、特徴が不十分な症候群である。過角化性EMは長期にわたる臨床経過をたどり、グルココルチコイド、アザチオプリン、および/またはシクロスポリンによる治療が試みられているが、寛解率は低い。 目的: 本研究の目的は、オクラシチニブ使用による2頭の犬のHKEMの成功した治療について説明することであった。 供試動物: 7歳、避妊雌、ハバニーズ(症例1)と1歳、停留精巣の雄、ダックスフンド(症例2)。 方法: 症例の特徴付けおよび臨床診断は、病変の特徴、外科的生検、細胞学的評価、培養、直接免疫蛍光法(DIF)、および治療に対する期待される反応に基づいた。 結果: どちらの症例も、付着性の鱗屑を伴う多巣性で、しばしば対称性の過角化性局面を示した。組織学的所見は、顕著な表皮過形成、不全角化性角化症、リンパ球性皮膚炎、およびリンパ球性サテライトーシスを伴う経皮アポトーシスを明らかにした。 DIFにより、細かいパッチ状のIgG、IgM、IgAの基底膜の沈着が明らかになった(症例2)。どちらの症例も経口オクラシチニブ(0.6–0.9 mg / kg 1日2回)で急速な改善を示し、症例1および2ではそれぞれ12週間および7週間で臨床症状の完全寛解が観察された。 結論と臨床的重要性: オクラシチニブは、犬のHKEMに即効性があり効果的な治療オプションと考えることができる。 摘要: 背景: 过度角化性多形红斑 (HKEM) 是一种临床上独特的皮肤病, 这种综合征的特征较少, 包括可能对称发生的过度角化性斑块, 以及类似于"典型"糜烂性犬EM的细胞凋亡。过度角化性 EM 的临床病程持久, 尽管已尝试使用糖皮质激素、硫唑嘌呤和/或环孢素治疗, 但缓解率较低。 目的: 报告使用奥拉替尼成功治疗的两只HKEM患犬。 动物: 一只 7 岁、切除卵巢的哈瓦犬(病例 1)和一只 1 岁、未去势隐睾腊肠犬(病例 2)。 方法: 病例特征和临床诊断基于病变特征、外科活检、细胞学评价、培养、直接免疫荧光 (DIF) 和预期的治疗反应。 结果: 两个病例均表现出多灶性、通常对称的过度角化性斑块, 伴粘附性鳞屑。组织学的调查结果揭示了突出的表皮增生, 角化不全性过度角化病, 淋巴细胞性皮炎, 以及伴随淋巴细胞性卫星现象的跨表皮细胞凋亡。DIF 显示点、片状 IgG、IgM 和 IgA 基底膜沉积(病例 2)。口服给予奥拉替尼(0.6–0.9 mg/kg, 每日两次)后, 两只犬均表现出快速改善, 在病例 1 和 2 中, 分别在 12 周和 7 周内观察到临床体征完全缓解。 结论和临床意义: 奥拉替尼可被认为是犬 HKEM 的一种速效和有效的治疗选择。 Resumo: Contexto: O eritema multiforme hiperqueratótico (HKEM) é uma dermatose clinicamente distinta e uma síndrome pouco caracterizada, composta por placas hiperqueratóticas com simetria e apoptose variáveis ​​semelhantes ao EM canino erosivo "clássico". O EM hiperqueratótico apresenta um quadro clínico prolongado e, apesar de tratamentos com glicocorticóides, azatioprina e/ou ciclosporina tenham sido tentados, as taxas de remissão são baixas. Objetivos: Descrever o tratamento bem‐sucedido do HKEM em dois cães usando oclacitinib. Animais: Um cão Havanese de 7 anos, castrado (Caso 1), e um cachorro Dachshund com criptorquidia intacto de 1 ano (Caso 2). Métodos: A descrição do caso e o diagnóstico clínico foram baseados nas características da lesão, biópsia cirúrgica, avaliação citológica, cultura, imunofluorescência direta (IFD) e respostas esperadas aos tratamentos. Resultados: Ambos os casos apresentaram placas hiperqueratóticas multifocais, muitas vezes simétricas, com escama aderida. Os achados histológicos revelaram hiperplasia epidérmica proeminente, hiperqueratose paraqueratótica, dermatite linfocítica e apoptose transepidérmica com satelitose linfocítica. A IFD revelou depósitos finos e irregulares de IgG, IgM e IgA na membrana basal (Caso 2). Ambos os cães apresentaram melhora rápida com oclacitinib oral (0, 6‐0, 9 mg / kg duas vezes ao dia) com remissão completa dos sinais clínicos observados em 12 e sete semanas nos casos 1 e 2, respectivamente. Conclusão e importância clínica: Oclacitinib pode ser considerado uma opção de tratamento de ação rápida e eficaz para HKEM em cães.